Pengaruh Media Sosial dalam Peningkatan Kesiapsiagaan dan Respon Bencana pada Mahasiswa - Hayati, Hayati; Wirda, Wirda; Mauvizar, Erly (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to analyze the influence of social media on improving disaster preparedness and response among STIKES Muhammadiyah Aceh students. The approach used is quantitative with the cross-sectional method, where research is carried out at a specific point in time. Informants were selected using random sampling, and data were collected through a Guttman scale questionnaire that offered